Student Readiness and Experiences in Blended Learning: Implications for Sustainable Education in Bangladesh (Dhaka University Journal of Business Studies, 2026)
The global disruption of education caused by the COVID-19 pandemic has accelerated the adoption of blended learning worldwide. However, despite this growth, many students continue to lack the necessary knowledge and readiness for effective engagement in blended learning environments. This gap poses significant challenges to the implementation of blended learning. This study investigates the readiness and experiences of students in Bangladesh with blended learning. It develops and validates a theoretical framework to identify the key factors influencing the experience, readiness, and outcomes of blended learning. The research also explores the role of social support and learner attitudes in enhancing engagement and success. Additionally, the study advocates for the integration of the Rocketship Education model to help bridge digital divides through personalized and adaptive learning approaches. The findings have practical implications for the design of effective blended learning programs, improving graduate employability, advancing Sustainable Development Goals (SDGs), and preparing students for the 21st-century workforce.Journal of Business Studies, Vol. XLIV, No. 1, 2025 Page 211-238